Use of antidepressants and benzodiazepine-related hypnotics before and after initiation of TNF-α inhibitors or non-biological systemic treatment in patients with rheumatoid arthritis, psoriatic arthritis or ankylosing spondylitis - Philip Brenner; Anna Citarella; Louise Wingård; Anders Sundström (BMC Rheumatology, 2020)
Abstract Background Rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) are autoimmune disorders associated with an increased risk for depression, anxiety and sleeping problems. The objective of this study was to analyze use of antidepressants and benzodiazepine-related hypnotics (BRH) in Sweden before and after first time treatment with anti-TNF and non-biological systemic (NBS) treatments among patients with the above diagnoses, and to correlate such use with that of randomly selected population controls. Methods Patients and dispensed drugs were identified in nationwide Swedish healthcare registers. Proportions of subjects filling prescriptions of antidepressants and BRH from 2 years before start of treatment (index-date), and 2 years after index date were assessed. Using the period -6 months to index-date as reference, prevalence rate ratios were computed for 6 months’ intervals before and after index. For up to ten randomly selected population controls per patient, the same measures were calculated. Results A total of 6256 patients started anti-TNF treatment, and 13,241 NBS treatment. The mean age at index was 52.0 for the anti-TNF group and 56.1 for NBS. Use of antidepressants and BRH was similar in both treatment groups (10.4–12.8%), significantly more common than in the controls (6.6 to 7.6%). For all patients, proportions filling prescriptions for antidepressants and BRH decreased directly or soon after the index; no such changes were seen in the controls, who all showed a slow but steady increase in use over time. Starters of anti-TNF treatment did not show clearer decreases in use of psychotropics than those initiating NBS. Conclusions Decreased rates of dispensed psychotropic drugs after the time of anti-TNF and NBS treatment initiation were seen among patients with autoimmune disorders but not population controls. This may correspond to treatment effects of anti-TNF and NBS also on psychiatric symptoms among these patients.